Organic vanadium compounds - Transition state analogy with organic phosphorus compounds - Crans, Debbie C.; Keramidas, Anastasios D.; Drouza, Chryssoula (My University, 1996)
Vanadium compounds, particularly in oxidation state V, are potent inhibitors of phosphoryl group transfer enzymes. In this paper the existance of a correlation between the coordination geometry of a series of vanadium dipicolinate complexes and their potency as inhibitors for chicken intestinal alkaline phosphatase is examined. We find that within a limited series of vanadium compounds the five-coordinate derivatives are the most potent inhibitors.
Keywords: Vanadium; Vanadates; Vanadyl sulfate